Transfer Of Character In The Digital Era (Holistic Analysis Of Education Institutions In Indonesia) - Syaifulloh Yusuf; Nurkhamimi Zainuddin (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
This study aims to reveal the phenomenon of learning in the digital era and examine the steps, obstacles, and results of the transfer of character in educational institutions in Indonesia. This research was conducted at Candirejo Elementary School, Sardonoharjo, Ngaglik, Sleman, Yogyakarta, Indonesia. This research method is qualitative with a phenomenological approach, and the data of this research was analyzed with holistic analysis. The results of this study indicate that the learning phenomenon at Candirejo Elementary School always follows government policy. Currently, the learning is carried out using PTMT (Limited Face-to-face Learning).Furthermore, the transfer of character at Candirejo Elementary School is carried out in several steps, such as sending material through the WhatsApp application, YouTube videos, and playing videos in class. Although the three strategies are still not maximally carried out, the teachers still attempt to provide character education values. The problem is that teachers cannot directly supervise when students study at home, so the role of parents is needed to help students study at home.